FORMULATION DEVELOPMENT OF MOUTH DISSOLVING PRINTED FILM OF KETOROLAC AND IN VITRO EVALUATION - KHAN, FARHEEN BANO; KILOR, VAISHALI; SAPKAL, NIDHI; DULE, PRIYA (International Journal of Applied Pharmaceutics, 2022)
Objective: The present research work was carried out to prepare Ketorolac printed Oral Thin Films using a pneumatic pressure printer. In this research, we attempted to prepare a non-contact printing system by using pneumatic pressure-based printer that incorporates printing of active pharmaceutical ingredients onto a medical-grade Orodispersible film for developing personalized medication. Methods: In the present work Ketorolac Trometamol was used as a model drug. Placebo substrate was developed by using cellulosic polymers like HPMC, MCC, Neusilin, and starch to impart paper-like properties that are desirable for printing. It was evaluated for various physicochemical properties like disintegration time, mechanical strength, folding endurance, surface properties, etc. Polymers and plasticizers were evaluated for the development of drug loaded Printing ink. The drug-printed films were characterized for physicochemical properties and in vitro drug dissolution. Results: Various film-forming polymers were evaluated for the development of printing substrates. The F3 substrate had desired mechanical properties i.e. the thickness of 0.157±0.003, the tensile strength of 0.331±0.016, disintegration within 60 seconds, and this substrate also maintained its integrity after the printing of the drug ink. The HPMC-based ink (I4) with polyethylene glycol for modulating flow properties of ink in the concentration of 1.40%w/v was selected among various ink formulations. The drug release from the printed films was 98±1.94% in 1 h. Conclusion: Through this new drug printing technology the limitation of low drug dose loading associated with ink-jet and flexographic printing can be solved by increasing the drug loading ranges from micrograms to milligrams by a single pass of the print head.